Preliminary experimental study on a novel device using biomaterial for shunting fibrotic bleb following Ahmed glaucoma valve surgery in dogs - Songhui Lee; Du-Min Go; Eunji Lee; Dae-Yong Kim; Kangmoon Seo; Seonmi Kang (Scientific Reports)
Abstract This study aimed to design and evaluate a novel trans-bleb device (TBD) for draining aqueous humor trapped within fibrotic blebs following Ahmed glaucoma valve (AGV) implantation in dogs. Two clinically normal, purpose-bred Beagles underwent AGV implantation surgery in one eye. When a bleb was formed with increased intraocular pressure (IOP), the TBD was inserted through a fenestration created in the bleb. IOP measurements, slit-lamp biomicroscopic and ultrasound biomicroscopic (UBM) evaluations were performed during follow-up. Results showed that IOP in the eyes undergoing AGV surgery was significantly lower than in the contralateral normal eye (P < .001). After 3 weeks, the IOP increased, and the UBM examination confirmed the presence of a bleb wall and an underlying cavity. After TBD application surgery, a significant decrease in IOP was observed (P < .001). Histological findings indicated that the TBD effectively penetrated the fibrotic membrane surrounding the AGV, with observed mild inflammatory cell infiltration, neovascularization, and myofibroblast differentiation, suggesting filtering bleb formation. The TBD may offer a novel approach to address bleb fibrosis-related failure following glaucoma surgery, restoring aqueous humor flow, and thus reducing IOP. Further research is needed to validate its effectiveness, optimize its design, and assess long-term outcomes.